Mycorrhiza application improves rice morpho-physiological traits in different soil water content - Mahmudi Mahmudi; Radian Radian; Safriadi Safriadi; Singgih Tiwut Atmojo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Mycorrhizal fungi are beneficial soil microorganisms that establish mutualistic associations with plant roots, significantly enhancing nutrient and water uptake under abiotic stress conditions. In West Kalimantan, limited soil water content frequently constrains rice cultivation, negatively impacting plant growth and yield. This study aimed to evaluate the effects of mycorrhizal inoculation on the morphophysiological traits of rice under varying levels of soil water content. The experiment was conducted from February to June 2022 in Mempawah Regency, West Kalimantan, using a split-split-plot randomized complete block design. The main plot factor was mycorrhizal inoculation (inoculated and uninoculated), the subplot factor was soil water content (100%, 80%, and 60%), and the sub-subplot factor was rice variety (Inpari 32 and Inpari 42). The results demonstrated that mycorrhizal inoculation significantly improved rice tolerance to moderate drought stress through adaptive morphophysiological mechanisms. This was indicated by increased phosphorus uptake efficiency and enhanced net assimilation rate, even at 60% soil water content. These physiological improvements contributed to better plant morphological development, including greater plant height (84.73 cm), dry biomass (8.36 g), number of panicles (15.83 panicles), panicle length (22.21 cm), number of grains per panicle (189.96 grains), and grain weight per clump (72.31 g). Keywords: mutualistic associations; mycorrhizal inoculation; physiological improvements; rice tolerance